Hypoxic regulation of osteoclast differentiation and bone resorption activity - Knowles, H (Dove Medical Press, 2015)
Bone integrity is maintained throughout life via the homeostatic actions of bone cells, namely, osteoclasts, which resorb bone, and osteoblasts, which produce bone. Disruption of this balance in favor of osteoclast activation results in pathological bone loss, which occurs in conditions including osteoporosis, rheumatoid arthritis, primary bone cancer, and cancer metastasis to bone. Hypoxia also plays a major role in these conditions, where it is associated with disease progression and poor prognosis. In recent years, considerable interest has arisen in the mechanisms whereby hypoxia and the hypoxia-inducible transcription factors, HIF-1α and HIF-2α, affect bone remodeling and bone pathologies. This review summarizes the current evidence for hypoxia-mediated regulation of osteoclast differentiation and bone resorption activity. Role(s) of HIF and HIF target genes in the formation of multinucleated osteoclasts from cells of the monocyte–macrophage lineage and in the activation of bone resorption by mature osteoclasts will be discussed. Specific attention will be paid to hypoxic metabolism and generation of ATP by osteoclasts. Hypoxia-driven increases in both glycolytic flux and mitochondrial metabolic activity, along with consequent generation of mitochondrial reactive oxygen species, have been found to be essential for osteoclast formation and resorption activity. Finally, evidence for the use of HIF inhibitors as potential therapeutic agents targeting bone resorption in osteolytic disease will be discussed.